Rentenkapitalismus und Stadtentwicklung im islamischen Orient - Ehlers, Eckart (ERDKUNDE, 1978)
On the basis of Bobek's concept of rent capitalism this essay seeks to explain the mechanism of urban growth, urban hierarchies and the relations of towns and their surrounding areas in Iran. The pre-industrial town is distinguished from its agrarian Umland by a number of characteristics (property relationships of land and soil, processing of agricultural produce, supplying of rural areas etc.), all of which are of advantage to the town. Inter-urban relations,analysed on the basis of the national distribution of goods, as well as the organisation of cottage industry and manufacturing arrangements, are characterised by the pre dominance of the large cities; small and medium-sized towns function as bridgeheads for the economic interests of large towns. The industrialisation which has been observed since 1930 has promoted this trend. The concluding discussion of the justification of an independent economic and social stage of rent capitalism is conducted in such a way as to acknowledge rent capitalism as a specific indicator of the Islamic Orient. Thus the validity postulated by Bobek is subjected to a considerable limitation in respect of time and space.